AB0502 Long-term follow-up of esophageal diameter in patients with anti-centromere antibody sero-positive systemic sclerosis and primary sjögren's syndrome. (23rd January 2014) - Hashimoto, N.; Kuno, H.; Kitano, M.; Iwasaki, T.; Sano, H.; Hashimoto, T.
Abstract : Background: Anti-centromere antibodies (ACA) are characteristic autoantibodies which are detected in patients with systemic sclerosis (SSc) and primary Sjögren's syndrome (pSS). We previously reported that ACA are a useful marker of esophageal dilatation in patients with SSc (EULAR2010). Objectives: The aim of this study was to examine the role of ACA for esophageal dysfunction in patients with SSc and pSS using the barium esophagogram during long-term follow up. Methods: Twelve ACA sero-positive pSS (ACA+/pSS) and 20 ACA sero-positive SSc (ACA+/SSc) patients were studied. Barium esophagogram was performed in all ACA+/pSS and ACA+/SSc patients by receiving 4 successive swallows of 20 ml of barium at 30 sec intervals in the standing position. The esophageal dilatation was examined by measurement of maximal diameters at lower esophagus by a single blinded observer. All ACA+/pSS and ACA+/SSc patients were evaluated for the presence of cutaneous subtype, interstitial pneumonia, joint involvement, chronic thyroiditis, primary biliary cirrhosis (PBC) and Raynoud's phenomenon. We also analyzed γ-globulin, rheumatoid factor (RF), anti-SS-A antibodies, anti-SS-B antibodies, anti-Topoisomerase I antibodies (Topo-I) and anti-U1 RNP antibodies in serum from all patients. The diagnosis of PBC was based on liver function test, the presence of serum anti-M2 antibodies and histopathological findings. Results: All ACA+/pSS and ACA+/SSc patients were women. Follow-up period (6.88±1.98 vs 7.14±1.63 years) and median age (64.8±11.2 vs 59.5±10.6 years) were not different between ACA+/pSS and ACA+/SSc patients. There was no significant difference between ACA+/pSS and ACA+/SSc patients in the prevalence of interstitial pneumonia, joint involvement, chronic thyroiditis, PBC, hyper γ-globulinemia and positivity of RF. However, the prevalence of anti-SS-A antibody and anti-SS-B antibody sero-positive patients were significantly higher in ACA+/pSS than in ACA+/SSc (66.7% vs 20.0%, p=0.008, 25.0 vs 0.0%, p=0.019). Anti-Topo-I antibodies and anti-U1 RNP antibodies were not detected in all patients. Although the esophageal diameters were not significantly different between these groups at the initial evaluation (22.1±2.5mm vs 26.6±8.4mm), they were significantly wider in ACA+/SSc patients than in ACA+/pSS patients at the end of follow-up (21.1±4.1mm vs 30.8±10.5mm, p=0.005). In addition, ACA+/SSc patients showed significant increase of the percentage change of esophageal diameters during follow-up when compared with ACA+/pSS patients (95.3% vs 119.5%, p=0.047). Conclusions: The present study demonstrated that esophageal dilatation was progressive in ACA sero-positive patients during long-term follow-up. However, the severity of esophageal dilatation depended on the underlying diseases. Another factor other than ACA seems to contribute to esophageal dysfunction. Disclosure of Interest: None Declared